The South African bread cartel: a single case study exploring the scope for responsive regulation of white-collar crime in a developing country - Patel, Varsha (Department of Public Law, 2025)
Criminology traditionally focused on street crimes. In 1939, Sutherland introduced the concept of white-collar crime, which encouraged criminologists to turn their attention to crimes of the rich and powerful. In particular, Australian researcher John Braithwaite has produced a large body of work on white-collar crime. Braithwaite is critical of the professionalisation of criminology that marginalises the community from regulatory activities. Braithwaite argues that the business and community sectors should play a more significant role in regulating white collar crime within conventional justice systems. According to Braithwaite, community activists and industry watchdogs can play a role in holding white-collar criminals accountable and possibly elicit restorative overtures for victims. Braithwaite acknowledges that his model is ideally suited to a developed state with the financial resources and skills to establish and oversee alternative processes. However, he suggests that his model can be adapted to developing spaces by leveraging the capacity embedded in business and community sectors and augmenting deficiencies by partnering with international groups. Recently, the actions of a whistle-blower, supported by civil society mobilisation, exposed the South African Bread Cartel and led to hefty fines for the cartelists, legislative amendments and the development of class action jurisprudence. The bread cartel case demonstrates how communities can contribute to regulating cartels. This dissertation is a single case study of the bread cartel that investigates whether responsive regulation finds resonance in South Africa. Several semi-structured, in depth interviews were conducted. The data was analysed thematically and explored themes like industry bodies, community activism and restorative justice. The findings are surprising. The success of the South African Bread Cartel seems almost accidental. The relationships between and the normative values of the state, business and community sectors appear to influence the scope for responsive regulation. In addition to capacity constraints across sectors, contextual factors like historical legacies and the size and shape of the economy may determine the scope for responsive regulation of white-collar crime in a developing country like South Africa. Such findings provide a map to guide future research.